Reescritas da nação: uma leitura de Cuando ya no importe - Viviane Monteiro Maroca (2016)
This thesis aims to focalize the rewritings of national imaginary in Past Caring, last novel of Juan Carlos Onetti. Therefore, it was necessary to revisit womens representations in that context. Published during his exile in Spain, the novel is a fictional diary of an exiled man and portrays questions of identity that constitute this character and, at the same time, in an intimate and personal way, undertakes a destabilizing reading of the hegemonic speeches that have built the narrated nation. The work is divided into four chapters. In the first chapter discusses Latin Americas peripheral condition in face of the Occident and its impossibility of fully adhering to social-economical projects built by European modernity. In this sense, my attempt is to dialogue with the notions of "Latin American theoretical babbling" and post-occidental reason, conceived by Hugo Achugar and Walter Mignolo, respectively, which reclaim, each one in their own way, the liminality of Latin American thought, facing the alleged Western universality. These notions also articulate the discussion regarding representation and the loci of enunciation of subaltern subjects, aiming to vindicate their own speech, within a geo-historical sensitivity that bears their speeches. In the second chapter, womens representations are analysed regarding their phantasmal relations to the narrators identity. In the third chapter, a the main women characters are studied separately, but also aiming to understand how the novel dialogues with the XIX century project of romantic novels, in which families are thought as national allegories. Lastly, the representations of subaltern studies within the narrative are re-evaluated, as well as some myths that consolidated national imaginary, in order to observe if Past Caring belongs to the Uruguayan post-dictatorship project of dismantling national hegemonic narratives. To that effect, the diary is considered the space in which nation is narrated in its minimal unity; in which subjects are expressed in their heterogeneity, contrarily to the homogenization complied by the Latin American tradition of foundational epics and fictions.